Evaluation of a web-based mathematical problemsolving course using a constructivist approach / Hong Kian Sam, Lai Kim Leong and Tan Kock Wah - Hong, Kian Sam; Lai, Kim Leong; Tan, Kock Wah (Penerbit UiTM (UiTM Press), 2008)
This study was conducted to investigate the effectiveness of teaching a mathematical problem solving course via the Web using a constructivist approach. A total of 37 teacher trainees at teacher training institution were sampled. The participants were required to solve authentic mathematics problems in small groups of 4-5 participants based on the Polya's Model via e-conferencing in a Web-based course. The findings showed that there were no significant changes in the articipants' attitudes toward mathematics, while the participants' skills in problem solving for "understand the problem" and "devise a plan" based on the Polya's Model were significantly enhanced, though no improvement was apparent for "carry out the plan" and "review." The findings also showed that there were significant improvements in the participants' critical thinking skills.